Evaluation the level of vitamin D and its relationship with clinical symptoms in patients with COVID-19 referred to the medical center in Bam city - Mortazavi, Seyed Mojtaba; Khoshnood, Saeed; Faraji, Reza; Baravati, Rezvan Bagheri; Khalili, Hakime; Radfar, Ali; Jalali, Elham; Nezam Nia, Maria; Akrami, Sousan; Shirani, Maryam (German Medical Science GMS Publishing House, 2024)
Background: Vitamin D is a steroid hormone that protects against viral infections by influencing innate and adaptive immune responses. The effectiveness of vitamin D3 supplementation in COVID-19 is unknown. The study's goal was to elucidate the relationship between blood vitamin D levels and COVID-19 clinical outcomes by examining the effect of a single high dose of vitamin D3 on the length of hospital stay in patients. Methods: The descriptive, retrospective study was performed from March to May 2021 at a referral center for patients with COVID-19, in Bam, Iran. A checklist consisting of demographic variables was used to gather data, and laboratory assessments of serum 25(OH) D were evaluated and documented. The connection between serum vitamin D and patient clinical outcomes was investigated after patients were given a single oral dose of 200,000 IU of vitamin D3. Results: 71 COVID-19 patients were treated. Radiological results did not change substantially amongst individuals with various levels of 25(OH)D. After a single dosage of vitamin D3, mean blood levels of xyvitamin D increased considerably and the need for intubation and SpO decreased, and as did the respiratory rate in patients requiring hospitalization due to COVID-19. Conclusion: A single administration of 200,000 IU of vitamin D3 significantly reduced the severity of COVID-19.